2007
DOI: 10.1029/2006gl028936
|View full text |Cite
|
Sign up to set email alerts
|

Vertical distribution of hydrogen at high northern latitudes on Mars: The Mars Odyssey Neutron Spectrometer

Abstract: Neutron leakage currents measured using the Mars Odyssey Neutron Spectrometer are used to develop a two‐layer model of the distribution of hydrogen (here parameterized as water‐equivalent hydrogen, WEH) at high northern latitudes. The WEH abundance in the upper layer, Wup, was found to range between 1% and about 5%. The maximum value of the apparent thickness, D, of this upper layer peaks at about 60° latitude, giving the appearance of zonal bands of enhanced D in both hemispheres. This maximum is consistent w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
24
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 26 publications
4
24
0
Order By: Relevance
“…The pore ice created by diffusive back-filling extends close to equilibrium. The ice distribution that results from this climate scenario is consistent with the observed geographic distribution and burial depth of ice, but it is inconsistent with the high hydrogen content measured by neutron spectroscopy at high latitudes (Litvak et al, 2006;Feldman et al, 2004Feldman et al, , 2007, unless another mechanism operates to segregate ice after deposition and produces ice contents in excess of soil porosity (Fisher, 2005;Dash et al, 2006).…”
Section: Role Of Emplacement Timesupporting
confidence: 71%
See 2 more Smart Citations
“…The pore ice created by diffusive back-filling extends close to equilibrium. The ice distribution that results from this climate scenario is consistent with the observed geographic distribution and burial depth of ice, but it is inconsistent with the high hydrogen content measured by neutron spectroscopy at high latitudes (Litvak et al, 2006;Feldman et al, 2004Feldman et al, , 2007, unless another mechanism operates to segregate ice after deposition and produces ice contents in excess of soil porosity (Fisher, 2005;Dash et al, 2006).…”
Section: Role Of Emplacement Timesupporting
confidence: 71%
“…High ice concentrations, far in excess of porosity, are favored by neutron (Feldman et al, 2002(Feldman et al, , 2007(Feldman et al, , 2008Mitrofanov et al, 2002;Prettyman et al, 2004;Litvak et al, 2006), gamma-ray (Boynton et al, 2002), and radar (Mouginot et al, 2010) data, which points toward the presence of an ice sheet (Fig. 7b or c).…”
Section: Comparison With Observational Constraintsmentioning
confidence: 89%
See 1 more Smart Citation
“…It is most likely that these dark regions consist of water ice intimately mixed with lower albedo dust. This is consistent with the inferred composition of the North Polar Region deduced from neutron spectroscopy observations (Feldman et al, 2007). Near-infrared (NIR) data from the MRO Compact Reconnaissance Imaging Spectrometer for Mars (CRISM) also show strong NIR features of water ice in lower albedo units within the north polar layered deposits (Calvin et al, 2009).…”
Section: Large Scale Changes In Bright Depositssupporting
confidence: 65%
“…Even without high albedo, the polar dome is still composed mainly of water ice contaminated with dust (Feldman et al, 2007;Phillips et al, 2008;Calvin et al, 2009) Most regions undergoing variation are adjacent to large changes in elevation (scarps) which may be more prone to dust activity generated therein as well as to katabatic winds from the higher elevations of the polar dome; and seasonal CO 2 disappears from the residual north polar cap (RNPC) in late spring, around Ls = 75° (Langevin et al, 2005). In Cantor et al (2010), we showed that the visible Lambert albedo of areas when they darkened after solstice was almost identical to that of unfrosted regions elsewhere in the RNPC.…”
Section: Discussionmentioning
confidence: 99%